Terapi Aktivitas Kelompok (TAK) Melatih Stimulasi Sensori Menyanyi dan Menari Bersama Warga Disabilitas Mental Di Dusun Ru Wolong Desa Lela Kabupaten Sikka - Reong, Antonia Rensiana; Kuwa, Maria Kornelia Ringgi; Mane, Gabriel; Gaharpung, Mediatrix Santi; Carvallo, Yustina Thomasine; Dewi, Agnes Yuliana Asri; Lipi, Philipus (PPPM Stikes Banyuwangi, 2022)
Background: Efforts to improve services to improve the soul have been carried out by personnel, by conducting Group Activity Therapy (TAK) activities. The problems of 1000 souls that can be overcome through TAK are clients with social isolation, hallucinations, withdrawal and low selfesteem. The implementation of this activity aims to increase internal and external stimulation. As well as increasing a sense of caring, solidarity, and togetherness with people with mental disabilities. Method: Community Service Activities using mentoring intervention methods for students together with Nanga Community Health Center nurse partners provide Group Activity Therapy; sensory stimulation of singing and dancing with people with mental disabilities. Result: From the results of the evaluation of the implementation of TAK after being given Activity Therapy, it is known that from 7 participants who are able to socialize and follow the Directional leader as many as 6 people (85.7%) and who are not able to cooperate in participating in activities according to the Referral leader as many as 1 person (14.3%). Conclution: There are differences in social behavior responses before and after being given Group Activity Therapy.